PEMANFAATAN KUBIS UNGU (Brassica oleracea L) SEBAGAI INDIKATOR FERMENTASI KARBOHIDRAT PADA MEDIA UJI BIOKIMIA - Rochmanah Suhartati; Dewi Peti V; Fanzi Afsgar (Journal of Indonesian Medical Laboratory and Science, 2021)
Purple cabbage (Brassica oleracea L) contains anthocyanins that are soluble in 96% ethanol. These anthocyanin compounds can change color at acidic, neutral and alkaline pH. The color change can be used as an indicator of carbohydrate fermentation reaction in the biochemical test media for mannitol and lactose by utilizing ethanol extract of purple cabbage as an alternative acid-base indicator in liquid sugar medium. The research method used is experimental. The results showed that the purple cabbage extract solution could be used as an alternative acid-base indicator to see the results of the fermentation reaction of mannitol and lactose in the medium. The color change that occurs is from colorless to pink. Based on the results it can be concluded that the ethanol extract of purple cabbage can be used as a color indicator in the mannitol dan lactose carbohydrates fermentation test.